The Social Aspect of Indonesian Armed Forces in The Shift of National Defense System Paradigm - Priyanto; Asmoro, Novky (South Asian Journal of Social Sciences and Humanities, 2023)
The social aspect of Indonesian Armed Forces (Tentara Nasional Indonesia/TNI) cannot be separated from the shifting of national defense system paradigm. In term of civil-military relationship, it can be traced by the rise of civil service contribution such as government and non-government elements in anticipating future threats to the region. The perception of threat from global scope to regional scope as well as national has been interpreted as the threat to national security, which is a democratic government ruled by civilian based on good governance principles is supported by military in tackling the threat to national security and society. This paper will describe some developments of social aspects in the context of the change of state defense system. This paper will focus on analyzing the efforts of government for achieving accountable governance through assessing socio-political elements of national security. A conclusion will provide an overview in regard to the development of a conceptual model of existing military and civilian integration in the management of the transformation of the national security system to promote democracy in Indonesia..
Keywords: Social Aspect; Indonesian Armed Forces; National Defense System; Paradigm